Tourists’ Perception toward Traveling in Toraja Adrianus Surianto Girikallo, ST,MM - Adrianus surianto Girik Allo (UKI TORAJA, 2017)
A tourism destination is an important unit of analysis the difficult to define(Haywood, 1986), but may be considered as a cluster of interrelated stakeholdersembedded in a social network (Scott et al., 2008a). Such a network of stakeholdersinteracts, jointly meeting visitor needs and producing the experience that thetravellers consume. These destination stakeholders include accommodationbusinesses, attractions, tour companies, and others providing commercial services;government agencies and tourism offices as well as representatives of the localcommunityThis paper has adopted a complex network analysis perception to the study oftourismDestinations that deal with the tourism atractions, amenities, accessibilities andservieces to visit Toraja.Based on the result of analyisis can be stated that1. The natural view is the first interesting then followed by ceremonies.2. Lack facilities enjoyed by the tourist at every tourist destination.3. Poor of infrasture have been faced by travellers.Attraction. The paperhas also discussed a number of implications of the complexity of atourism destination system such as difficulty in forecasting and theconsequent need for adaptive management. A number of techniques andmeasures have also been presented which demonstrate that there arepractical means to analyse networks.